Power Estimation in College Campus by Using Renewable Energy Sources - Shivarudraswamy, Karan Vyasa, Vika Patel, Deekshitha S. Nayak (International Journal of Advanced Science and Technology, 2020)
The demand for biogas digester arises as a result of huge amount of food waste produced per day. Biogas digester that uses kitchen waste is 800 times more efficient than conventional biogas system. In MIT Manipal college campus, they have numerous student residences and messes, where an extensive measure of kitchen waste is obtained which can be used for better purposes. The production of Biogas needs anaerobic digestion. Hence, the biogas can reduce the dependency on LPG for cooking in all the messes. Manipal is well illuminated region with maximum of 980 kWh/m2 radiation. The load of all the labs in the electrical department is calculated and based on the power demand, number of solar panels is estimated. Further, simulation of a model containing photo voltaic arrays, battery, battery controller, MPPT controller and inverter along with filter to supply 124 kW of power is carried out.